Webinars for English Language Teachers During the Pandemic: Global Perspectives on Transitioning to Remote Online Teaching - Joan Kang Shin; Jered Borup; Michael K. Barbour; Rocio V. Quiroga Velasquez (SAGE Publishing, 2022)
The current pandemic closed schools worldwide, tasking teachers to engage learners remotely without time to prepare. This study focuses on a professional development webinar series for English language teachers worldwide. Access to geographically dispersed English language teachers created an opportunity to gain international perspectives on teachers' challenges, perceptions, and needs related to transitioning to remote, online teaching. We found webinars were an effective way to provide just-in-time professional development for teachers globally, particularly about engaging students, providing feedback, developing online presence, and creating activities specific for online learning environments. The main challenges teachers reported facing were keeping their students engaged and progressing in the learning activities; unequal student access to technology and the internet; and learning and troubleshooting technology. At the same time, learning new technology and online resources was also what teachers most frequently reported enjoying about remote teaching.